Accelerating Promotional Media on Social Media for Brand Awareness Forest Smoothie - Suria Ningsih; I Nyoman Yoga Sumadewa; Ni Putu Sinta Dewi (International Journal of Economic, Finance and Business Statistics, 2024)
With high deforestation rates, reforestation is important to restore the ecosystem. Forest Smoothie, an international beverage company with the concept of "buying a smoothie equals planting a tree", faced the problem of lack of brand awareness on Instagram. Observation shows that their Instagram feed is monotonous and inconsistent in design, typography, and colour. This research aims to redesign Forest Smoothie's social media promotion with a modern and attractive design, using bright colours, consistent typography, and illustrations that reflect the brand's character. Using the design sprint method, this research went through the understand, diverge, decide, prototype, and validate stages. The result is an Instagram feed template that effectively attracts audience engagement. Validation through questionnaires showed positive responses regarding the recognizable concept, colour, typography readability, consistency, and interaction.